Energy absorption characteristics of multi-frusta configurations under axial impact loading. (January 2018) - Gan, Ning; Yao, Song; Dong, Haipeng; Xiong, Yulin; Liu, Dongrun; Pu, Dong
Abstract: In this study, the behavior of multi-frusta configurations under axial loading was analyzed, the effect of column spacing, number of tubes, shells, and cone combinations investigated, and multi-objective optimization applied to obtain optimal multi-frusta configurations. The results obtained indicate that the interaction between multi-frusta configurations without shell improves the system's specific energy absorption (SEA), the SEA of multi-frusta tubes can be improved by the rigid outer shell, and the overall energy absorption of restricted size structures benefit from having an appropriate number of multi-frusta configurations. They also show that cross-arranged tapers offer better energy absorption characteristics than other arrangements. Highlights: Multi-frusta configurations structures for energy absorption is proposed in this paper. The effects of multiple parameters are considered to study the crashworthiness of multi-frusta configurations. Multiobjective optimization design for multi-frusta configurations under axial impact loading was conducted.